Interactions of norharman and harman with DNA. - Hayashi, K (1977)
The interactions of norharman (9H-pyrido [3,4-b] indole) and harman (1-methyl-9H-pyrido [3,4-b] indole) with DNA were studied. DNA caused remarkable fluorescence quenching and change in the absorption spectra of the dyes. Scatchard plots obtained by optical titration gave Kd values of 2.2 X 10(-5)M and 7.7 X 10(-6)M, and apparent numbers of binding sites of 0.13/base and 0.12/base for norharman and harman, respectively. Agarose gel electrophoresis of circular DNA, closed in the presence or absence of norharman revealed that the dye intercalates DNA, thereby causing 17 +/- 3 degrees unwinding of the double helix.